Compound and preparation method thereof, hole transport material and perovskite solar cell

By developing a polyacrylate compound containing aniline fluorene or dianiline groups as a hole transport material, the problems of instability, low performance and high cost in existing perovskite solar cells have been solved, and efficient and stable perovskite solar cells have been achieved.

CN119505050APending Publication Date: 2025-02-25JINKO SOLAR (SHANGRAO) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411648973.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The hole transport materials in existing perovskite solar cells are unstable, have low performance, high cost and have poor applicability with perovskite solar cells.

Method used

A novel compound is provided, a polyacrylate polymer containing aniline fluorene or dianiline group in the structure, and the compound is prepared as a hole transport material by a specific synthetic method.

Benefits of technology

This compound has high decomposition temperature, good thermal stability, excellent film formation and high hole mobility, which can improve the performance and stability of perovskite solar cells and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505050A_ABST
    Figure CN119505050A_ABST
Patent Text Reader

Abstract

The invention discloses a compound and a preparation method thereof, a hole transport material and a perovskite solar cell, and belongs to the technical field of materials. The structure of the compound is as follows: # imgabs0 # 10lt; nlt; 10000, and n is an integer; and Ar is an aniline fluorene group or a diphenylamine group. The preparation method comprises the following steps: reacting dithienopyrrole, 4-bromobenzaldehyde and a catalyst I to obtain an intermediate I; reacting the intermediate I with bromo-succinimide to obtain an intermediate II; reacting the intermediate II, aniline fluorene or diphenylamine substances and a catalyst II to obtain an intermediate III; reacting the intermediate III with sodium borohydride to obtain an intermediate IV; reacting the intermediate IV with acryloyl chloride to obtain an intermediate V; mixing and reacting the intermediate V and an initiator to obtain the compound. As a hole transport material, the compound is relatively high in decomposition temperature, high in stability, good in film-forming property and good in mobility, and is beneficial to the photoelectric conversion effect of a perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a compound and a preparation method thereof, a hole transport material and a perovskite solar cell. Background Art

[0002] Perovskite solar cells (PSCs) are devices that use perovskite-type organic metal halide semiconductors as light-absorbing materials to directly convert light energy into electrical energy through the photovoltaic effect. Among them, trans-structured PSCs show great potential in commercial applications. The continuous development of new hole transport materials is a key factor in the preparation of efficient and stable perovskite solar cells. Polymer hole transport materials have great potential in realizing large-area trans-perovskite solar cells due to their excellent film-forming properties and solvent resistance, as well as low-cost printing technology.

[0003] In inverse perovskite solar cells, hole transport materials, as important transport layer materials between the perovskite layer and the transparent electrode, are not only responsible for the extraction and transport of holes and blocking the flow of electrons, but also directly affect the crystallization and film-forming properties of perovskite, playing a decisive role in improving battery performance and realizing large-scale commercial applications.

[0004] At present, HTMs in perovskite solar cells are mainly divided into three categories: inorganic hole transport materials, organic small molecule hole transport materials and organic polymer hole transport materials. Polymer hole transport materials have become important charge transport layer materials commonly used in trans-perovskite solar cells due to their excellent film-forming properties, high mobility and strong solvent tolerance. Nowadays, poly (3-hexylthiophene) (P3HT), poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA) and poly (3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) are the most commonly used polymer HTMs in the research of trans-perovskite cell devices. However, these commonly used polymer hole transport materials still have some defects that cannot be ignored, such as the inherent acidity and hygroscopicity of PEDOT:PSS, which will corrode and accelerate the degradation of perovskite materials, and affect the stability of trans-PSCs; the high cost of PTAA (1980$ / g), strong hydrophobicity, and insufficient HOMO energy level increase the instability and cost of the device. Therefore, it is still necessary to further develop new polymer HTMs to achieve low-cost, high-performance, stable, and large-area trans-PSCs. Summary of the invention

[0005] The main object of the present invention is to provide a compound, a preparation method thereof, a hole transporting material and a perovskite solar cell, so as to solve the problems of unstable hole transporting material, low performance, high cost and poor applicability to perovskite solar cells in the prior art.

[0006] To achieve the above object, according to one aspect of the present invention, there is provided a compound having a structure as shown in Formula 1:

[0007]

[0008] Wherein, 10 < n < 10000, and n is an integer;

[0009] Ar is an aniline fluorene group or a diphenylamine group.

[0010] Further, the structure of the aniline fluorene group is Formula 2 or Formula 3:

[0011]

[0012] The structure of the diphenylamine group is Formula 4 or Formula 5:

[0013]

[0014] According to another aspect of the present invention, there is provided a preparation method of the above compound, comprising the following steps:

[0015] Step S1: React dithienopyrrole, 4-bromobenzaldehyde and a catalyst under a nitrogen atmosphere to obtain Intermediate I;

[0016] Step S2: React Intermediate I with N-bromosuccinimide to obtain Intermediate II;

[0017] Step S3: React Intermediate II, an aniline fluorene or diphenylamine substance and a catalyst under a nitrogen atmosphere to obtain Intermediate III;

[0018] Step S4: React Intermediate III with sodium borohydride to obtain Intermediate IV;

[0019] Step S5: React Intermediate IV with acryloyl chloride to obtain Intermediate V;

[0020] Step S6: Mix Intermediate V with an initiator and react to obtain the compound.

[0021] Further, in Step S1, the molar ratio of dithienopyrrole, 4-bromobenzaldehyde and Catalyst I is (8 - 12):(11 - 15):(0.5 - 0.7).

[0022] Further, Catalyst I in Step S1 is palladium acetate and三叔丁基膦.

[0023] Furthermore, the molar ratio of palladium acetate to tri-tert-butylphosphine is 1:(1.5-2.5).

[0024] Furthermore, step S1 also includes a solvent.

[0025] Furthermore, in step S1, the solvent is toluene.

[0026] Furthermore, step S1 also includes an acid-base regulator.

[0027] Furthermore, in step S1, the acid-base regulator is sodium tert-butoxide, sodium carbonate, or potassium carbonate.

[0028] Furthermore, the reaction temperature in step S1 is 100° C. to 120° C., and the reaction time is 45 to 50 hours.

[0029] Furthermore, the product after the reaction in step S1 is purified to obtain intermediate I.

[0030] Furthermore, the purification process in step S1 includes: extracting, drying, filtering, distilling under reduced pressure and column chromatography on the product after the reaction in sequence to obtain intermediate I.

[0031] Furthermore, in step S2, the molar ratio of intermediate I to bromosuccinimide is 1:(1.5-2.5).

[0032] Furthermore, step S2 also includes a solvent.

[0033] Furthermore, in step S2, the solvent is tetrahydrofuran.

[0034] Furthermore, the reaction temperature in step S2 is -10°C to 10°C, and the reaction time is 1 to 5 hours.

[0035] Furthermore, the product after the reaction in step S2 is purified to obtain intermediate II.

[0036] Furthermore, the purification process in step S2 includes: extracting, drying, filtering, distilling under reduced pressure and column chromatography on the product after the reaction in sequence to obtain intermediate II.

[0037] Furthermore, in step S3, the molar ratio of the intermediate II, the aniline fluorene compound or the diphenylamine compound, and the catalyst II is (1.5-2.5): (4-6): (0.35-0.45).

[0038] Furthermore, the aniline fluorene compound is N-(4-methoxyphenyl)-9,9-dimethyl-9H-fluorene-3-amine or 9,9-dimethyl-N-(4-(methylthio)phenyl)-9H-fluorene-3-amine.

[0039] Furthermore, the diphenylamine compound is di(4-methoxyphenyl)amine or bis(4-(methylthio)phenyl)amine.

[0040] Furthermore, the catalyst II in step S3 is palladium acetate and tri-tert-butylphosphine.

[0041] Furthermore, the molar ratio of palladium acetate to tri-tert-butylphosphine is 1:(2.5-3.5).

[0042] Furthermore, the reaction temperature in step S3 is 75° C. to 100° C., and the reaction time is 4 to 8 hours.

[0043] Furthermore, step S3 also includes a solvent.

[0044] Furthermore, in step S3, the solvent is toluene.

[0045] Furthermore, step S3 also includes an acid-base regulator.

[0046] Furthermore, the acid-base regulator in step S3 is sodium tert-butoxide, sodium carbonate, or potassium carbonate.

[0047] Furthermore, the reaction temperature in step S3 is 60° C. to 100° C., and the reaction time is 20 to 30 hours.

[0048] Furthermore, the mixture after the reaction in step S3 is purified to obtain intermediate III.

[0049] Furthermore, the purification process in step S3 includes: extracting, drying, and column chromatography the mixture in sequence to obtain intermediate III.

[0050] Furthermore, the preparation step S3-1 of the aniline fluorene compound includes: mixing the fluorene compound, the aniline compound and the catalyst III, and reacting them to obtain the aniline fluorene compound.

[0051] Furthermore, the molar ratio of the fluorene compound, the aniline compound and the catalyst III is (3.5-4.5): (3.7-4.7): (0.35-0.45).

[0052] Furthermore, the catalyst III in step S3-1 is bis(diphenylphosphine)-ferrocene and tris(dibenzylideneacetone)dipalladium.

[0053] Furthermore, the molar ratio of bis(diphenylphosphine)-ferrocene to tris(dibenzylideneacetone)dipalladium in Catalyst III is 1:(1-1.1).

[0054] Furthermore, step S3-1 also includes a solvent.

[0055] Furthermore, in step S3-1, the solvent is toluene.

[0056] Furthermore, step S3-1 also includes an acid-base regulator.

[0057] Furthermore, the acid-base regulator in step S3-1 is sodium tert-butoxide, sodium carbonate, or potassium carbonate.

[0058] Furthermore, the reaction temperature in step S3-1 is 70°C to 90°C, and the reaction time is 20 to 28 hours.

[0059] Furthermore, in step S4, the molar ratio of intermediate III to sodium borohydride is 1:(9-11).

[0060] Furthermore, step S4 also includes a solvent.

[0061] Furthermore, in step S4, the solvent is tetrahydrofuran.

[0062] Furthermore, the reaction process in step S4 includes a first reaction process and a second reaction process.

[0063] The reaction temperature of the first reaction process is -10°C to 10°C, and the reaction time is 1 to 5 hours.

[0064] The reaction temperature of the second reaction process is 20°C to 35°C, and the reaction time is 10 to 15 hours.

[0065] Furthermore, the product after the reaction in step S4 is purified to obtain intermediate IV.

[0066] Furthermore, the purification process in step S4 includes: extracting, drying, filtering, distilling under reduced pressure, settling and filtering the product after the reaction in sequence to obtain intermediate IV.

[0067] Furthermore, in step S5, the ratio of intermediate IV to acryloyl chloride is 1 mmoL: (0.1-0.3) mL.

[0068] Furthermore, step S5 also includes a solvent.

[0069] Furthermore, in step S5, the solvent is dichloromethane and triethylamine.

[0070] Furthermore, the reaction temperature in step S5 is -10°C to 10°C, and the reaction time is 5 to 7 hours.

[0071] Furthermore, the product after the reaction in step S5 is purified to obtain intermediate V.

[0072] Furthermore, the purification process in step S5 includes: extracting, drying, filtering, distilling under reduced pressure, settling and filtering the product after the reaction in sequence to obtain intermediate V.

[0073] Furthermore, in step S6, the weight of the initiator is 0.5-1.5% of the weight of the intermediate V.

[0074] Furthermore, the initiator in step S6 is azobisisobutyronitrile.

[0075] Furthermore, step S6 also includes a solvent.

[0076] Furthermore, the solvent in step S6 is at least one of toluene, tetrahydrofuran and N-methylpyrrolidone.

[0077] Furthermore, the reaction process in step S6 includes a first reaction process and a second reaction process.

[0078] The reaction temperature of the first reaction process is 60°C to 75°C, and the reaction time is 2 to 4 hours;

[0079] The reaction temperature of the second reaction process is 55°C to 95°C, and the reaction time is 48 to 72 hours.

[0080] Furthermore, the product after the reaction in step S6 is purified to obtain the final compound.

[0081] Furthermore, the purification process in step S6 includes: sequentially performing n-hexane or ethanol / dichloromethane crystallization, suction filtration, drying, and acetone solvent extraction on the product after the reaction to obtain a compound.

[0082] According to a third aspect of the present invention, there is provided a hole transport material, which comprises the above compound or the compound prepared by the above preparation method.

[0083] According to a fourth aspect of the present invention, a perovskite solar cell is provided, comprising a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a conductive metal layer; wherein the material of the hole transport layer comprises the above-mentioned hole transport material.

[0084] Furthermore, the material of the conductive glass layer is ITO or FTO glass; the material of the conductive metal layer is a composite material of copper and gold.

[0085] Furthermore, the perovskite solar cell is an inverted perovskite solar cell.

[0086] By applying the technical solution of the present invention, the provided compound has a novel structure, low synthesis cost, good solubility, a simple preparation process, and is suitable for industrial production; the compound as a hole transport material has a high decomposition temperature, good thermal stability, good film-forming property, good wettability with perovskite precursor solvent, and is beneficial to the crystallization and film formation of perovskite; this type of polymer hole transport material has good mobility, is beneficial to the extraction and transport of holes, has a deeper HOMO energy level that matches that of perovskite, and can obtain good photoelectric conversion efficiency; this type of polymer hole transport material can be used in quasi-two-dimensional perovskite solar cells without being doped with any additives, and is repeatable, and this type of compound has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] The drawings in the specification, which constitute a part of this application, are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0088] Figure 1 The molecular structure H NMR spectrum of the compound MA-DTP-1 prepared in Example 1 of the present invention is shown;

[0089] Figure 2 The molecular structure H NMR spectrum of the compound MA-DTP-1 prepared in Example 1 of the present invention is shown;

[0090] Figure 3 The molecular structure H NMR spectrum of the compound MA-DTP-1 prepared in Example 3 of the present invention is shown;

[0091] Figure 4 The molecular structure H NMR spectrum of the compound MA-DTP-1 prepared in Example 3 of the present invention is shown;

[0092] Figure 5 A schematic diagram of the structure of an inverted perovskite solar cell prepared in Example 5 of the present invention is shown.

[0093] Reference numerals:

[0094] 1-ITO glass, 2-hole transport layer, 3-perovskite layer, 4-electron transport layer, 5-Cu / Au electrode layer. DETAILED DESCRIPTION

[0095] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0096] The present invention provides a compound, which is a polyacrylate polymer containing different side chain groups Ar, and the structure is shown in Formula 1:

[0097]

[0098] Among them, 10 < n < 10000, and n is an integer;

[0099] Ar is an aniline fluorene group or a diphenylamine group.

[0100] The molecular structure of the compounds provided by the present invention is novel, and they have good solubility in solvents such as dimethyl sulfoxide, N,N'-dimethylformamide, toluene, chlorobenzene, dichloromethane, etc.; the compounds have a relatively high decomposition temperature, excellent thermal stability; and good film-forming properties.

[0101] As a new hole-transporting material, the above compounds provided by the present invention contain acrylate structures in their molecular structures, and the O atoms therein can interact with Pb in the perovskite layer 2+ to enable the material to be stably applied in perovskite solar cells. The Ar long-chain thiophene-based benzoate structure contained in the molecular structure of the compound, as a multifunctional electron-rich thiophene-fused heterocyclic unit, has a more planar structure and more heteroatoms. The p orbitals occupied by the heteroatoms N and S are conjugated with the p orbitals of the aromatic structure, enhancing the π-π stacking of the molecule, providing stronger electron-donating properties, making the benzoate structure a p-type semiconductor, contributing to improving the stability of the molecule, having the unique characteristics of small reorganization energy, high mobility, chemical modification of N and thiophene sites, and interaction with metal ions; at the same time, the S atom can interact with Pb in the perovskite 2+ to have a certain interaction, which can passivate the interface defects on the surface of the perovskite, inhibit the non-radiative recombination at the interface, contribute to the improvement of the performance during PCSs, directly endow the HTMs with the interface passivation function, which will be more conducive to simplifying the device preparation process of PCSs and reducing the device preparation cost; moreover, the electron-rich N atom in the benzoate structure can improve the stability of the organic semiconductor material in the oxidized state, making the optoelectronic device have long-term operation stability.

[0102] The above compounds provided by the present invention, when used as hole-transporting materials in perovskite solar cells, have good mobility, which is beneficial to the extraction and transport of holes, have good wettability with the perovskite precursor solvent, are beneficial to the crystallization and film formation of perovskite, have a HOMO energy level that matches the perovskite and is relatively deep, have good photoelectric conversion efficiency, can be used in inverted quasi-two-dimensional perovskite solar cells without doping any additives and have repeatability.

[0103] As a specific embodiment, the structure of the aniline fluorene group is Formula 2 or Formula 3:

[0104]

[0105] The structure of the diphenylamine group is Formula 4 or Formula 5:

[0106]

[0107] In the Ar structures shown in Formula 2 to Formula 4 of the present invention, both aniline and fluorene contain aromatic groups, and aniline contains N, O or S atoms, which can react with Pb in the perovskite. 2+ The interaction can improve the stability of perovskite battery materials.

[0108] According to another aspect of the present invention, there is provided a method for preparing the above compound, comprising the following steps:

[0109] Step S1: reacting dithienopyrrole, 4-bromobenzaldehyde and a catalyst under nitrogen conditions to obtain intermediate I;

[0110] Step S2: reacting intermediate I with bromosuccinimide to obtain intermediate II;

[0111] Step S3: reacting the intermediate II, aniline fluorene or diphenylamine substances and a catalyst under nitrogen conditions to obtain the intermediate III;

[0112] Step S4: reacting intermediate III with sodium borohydride to obtain intermediate IV;

[0113] Step S5: reacting intermediate IV with acryloyl chloride to obtain intermediate V;

[0114] Step S6: Mix the intermediate V and the initiator, and react to obtain a compound.

[0115] The preparation method provided by the present invention is simple to operate and has low synthesis cost, can successfully synthesize the above-mentioned compound, and is suitable for industrial production.

[0116] The above-mentioned synthesis process of the present invention is shown in Formula 6:

[0117]

[0118] As a specific implementation manner, in step S1, the molar ratio of dithienopyrrole, 4-bromobenzaldehyde and catalyst I is (8-12): (11-15): (0.5-0.7); within the molar ratio range, the ratio of dithienopyrrole can be any value among 8, 9, 10, 11, 12 or a range value between any two of them, the ratio of 4-bromobenzaldehyde can be any value among 11, 12, 13, 14, 15 or a range value between any two of them, and the ratio of catalyst I can be any value among 0.5, 0.6, 0.7 or a range value between any two of them; using the above-mentioned raw material ratios, dithienopyrrole and 4-bromobenzaldehyde (a) can be catalyzed by the catalyst I to connect the benzaldehyde group to the N atom of pyrrole in the dithienopyrrole molecular structure.

[0119] As a specific implementation, the catalyst I in step S1 is palladium acetate and tri-tert-butylphosphine, and further, the molar ratio of the two is 1:(1.5-2.5); other types of catalysts can also be selected and the ratio can be adjusted according to actual needs, as long as the reaction of step 1 can be achieved.

[0120] As a specific embodiment, step S1 also includes a solvent, such as toluene, which is conducive to dissolving the reaction raw materials such as dithienopyrrole and 4-bromobenzaldehyde; it also includes an acid-base regulator, such as sodium tert-butoxide, sodium carbonate, and potassium carbonate; the pH of the reaction system is adjusted by the regulator to facilitate the reaction; the amount of the acid-base regulator can be adjusted according to the actual reaction situation, for example, the molar ratio of dithienopyrrole, 4-bromobenzaldehyde, catalyst I and acid-base regulator is (8-12): (11-15): (0.5-0.7): (14-16), wherein the ratio of the acid-base regulator can be any value among 14, 15, 16 or a range value between any two of them.

[0121] As a specific implementation manner, the reaction temperature in step S1 is 100°C to 120°C, and the reaction time is 45 to 50 hours; for example, the reaction temperature can be any value among 100, 105, 110, 115, 120, or a range value between any two of them; in the reaction process, the reactants are heated and condensed and refluxed, and the condensation and reflux time is any value among 45, 46, 47, 48, 49, 50 hours, or a range value between any two of them; the reaction of step S1 can proceed smoothly only at this heating temperature, too low a temperature cannot promote the reaction, and too high a temperature is easy to react and produce other non-target products, affecting the overall process.

[0122] As a specific implementation method, the product after the reaction in step S1 is purified to obtain intermediate I; the purification process includes: extracting, drying, filtering, vacuum distillation and column chromatography on the product after the reaction in sequence to obtain intermediate I; further, the crude reaction product is cooled to room temperature, the mixture is extracted with DCM, the organic phase is dried with anhydrous Mg2SO4, filtered, vacuum distilled, and finally purified by column chromatography (PE:DCM=10:1) to obtain a high-purity solid powder of intermediate I.

[0123] As a specific implementation manner, in step S2, the molar ratio of intermediate I to bromosuccinimide (NBS) is 1:(1.5-2.5); within this ratio range, the molar ratio of NBS can be any value among 1.5, 1.8, 2.0, 2.2, 2.5 or any range value between two of them; using this raw material ratio, after the reaction, a Br atom can be introduced into each of the thiophene groups on both sides of the dithienopyrrole.

[0124] As a specific embodiment, step S2 also includes a solvent, such as tetrahydrofuran THF, for dissolving NBS, and the ratio of the solvent to the reaction raw materials is 1 moL: (1.5-2.5) moL: (15-25) mL of intermediate I, bromosuccinimide (NBS), and THF. The amount of THF can be adjusted according to the actual dissolution situation.

[0125] As a specific implementation manner, the reaction temperature in step S2 is -10°C to 10°C, and the reaction time is 1 to 5h; for example, the reaction temperature can be any value among -10°C, -5°C, 0°C, 5°C, 10°C, or a range value between any two thereof, and the reaction time can be any value among 1h, 2h, 3h, 4h, 5h, or a range value between any two thereof.

[0126] As a specific implementation method, the product after the reaction in step S2 is purified to obtain intermediate II; the purification process includes: extracting, drying, filtering, vacuum distillation and column chromatography on the product after the reaction in sequence to obtain intermediate II; further, the crude reaction product is quenched with deionized water, the mixture is extracted with DCM, the organic phase is dried with anhydrous Mg2SO4, filtered, vacuum distilled, and finally purified by column chromatography (PE:DCM=6:1) to obtain a high-purity solid powder of intermediate II.

[0127] As a specific implementation manner, in step S3, the molar ratio of intermediate II, aniline fluorene compound or diphenylamine compound (either of the two compounds is used), and catalyst II is (1.5-2.5): (4-6): (0.35-0.45); within this ratio range, the molar ratio of intermediate II can be any value among 1.5, 1.8, 2.0, 2.2, 2.5, or a range value between any two of them; the molar ratio of aniline fluorene compound or diphenylamine compound can be any value among 4, 4.5, 5.0, 5.5, 6.0, or a range value between any two of them; the molar ratio of catalyst II can be any value among 0.35, 0.39, 0.4, 0.42, 0.45, or a range value between any two of them.

[0128] The present invention adopts the above-mentioned ratio range, and the intermediate II, the aniline fluorene compound or the diphenylamine compound are subjected to the catalytic reaction of the catalyst II, and the Br atom on the dithiophene is replaced by an Ar long side chain group, and the Ar side chains are respectively introduced into the thiophene structures on both sides of the dithiophene pyrrole molecular structure. As a multifunctional electron-rich thiophene fused heterocyclic unit, it has a more planar structure and more heteroatoms. The p orbitals occupied by the heteroatoms N and S are conjugated with the p orbitals of the aromatic structure, which enhances the π-π stacking of the molecule and provides a stronger electron-donating property, so that the benzoate structure becomes a p-type semiconductor, which helps to improve the stability of the molecule, and has the unique characteristics of small reorganization energy, high mobility, chemical modification of N and thiophene sites, and interaction with metal ions; at the same time, the S atom can react with the Pb in the perovskite. 2+ There is a certain interaction, which can passivate the interface defects on the perovskite surface and inhibit the non-radiative recombination of the interface, which is helpful to improve the effect during PCSs. Directly giving HTMs interface passivation function will be more conducive to simplifying the device preparation process of PCSs and reducing the device preparation cost.

[0129] As a specific implementation, in step S3, the aniline fluorene compound is selected from N-(4-methoxyphenyl)-9,9-dimethyl-9H-fluorene-3-amine and 9,9-dimethyl-N-(4-(methylthio)phenyl)-9H-fluorene-3-amine; the diphenylamine compound is selected from di(4-methoxyphenyl)amine or bis(4-(methylthio)phenyl)amine. The aniline fluorene compound or diphenylamine as the reaction raw material of the present invention can be selected from the prior art or synthesized.

[0130] As a specific implementation manner, the catalyst II in step S3 is palladium acetate and tri-tert-butyl phosphine; the molar ratio of palladium acetate to tri-tert-butyl phosphine is 1:(2.5-3.5), and the molar ratio of tri-tert-butyl phosphine can be any value among 1.5, 2.8, 3.0, 3.2, 3.5 or any range value between the two; other similar catalysts can also be selected and the ratio of the two can be adjusted, as long as the reaction of step S3 can be achieved.

[0131] As a specific implementation manner, the reaction temperature in step S3 is 75°C to 100°C, and the reaction time is 4 to 8h; for example, the reaction temperature can be any value among 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or a range value between any two thereof; the reaction time can be any value among 4h, 5h, 6h, 7h, 8h, or a range value between any two thereof.

[0132] As a specific implementation, step S3 also includes a solvent, such as toluene; and also includes an acid-base regulator, such as sodium tert-butoxide, sodium carbonate, and potassium carbonate.

[0133] As a specific implementation method, the mixture after the reaction in step S3 is purified to obtain intermediate III; the purification process includes: extracting, drying, and column chromatography the mixture in sequence to obtain intermediate III; specifically, the reaction product is cooled to room temperature and column chromatography is performed with PE / DCM of 6 / 1 to obtain intermediate III.

[0134] As a specific implementation, the preparation step S3-1 of the aniline fluorene compound includes: mixing a fluorene compound, an aniline compound and a catalyst III, and reacting them to obtain the aniline fluorene compound.

[0135] As a specific embodiment, the molar ratio of the fluorene compound, the aniline compound and the catalyst III is (3.5-4.5): (3.7-4.7): (0.35-0.45); within this ratio range, the molar ratio of the fluorene compound can be any value among 3.5, 3.8, 4.0, 4.2, 4.5 or a range value between any two of them; the molar ratio of the aniline compound can be any value among 3.7, 4.0, 4.2, 4.5, 4.7 or a range value between any two of them; the molar ratio of the catalyst III is any value among 3.5, 3.8, 4.0, 4.2, 4.5 or a range value between any two of them.

[0136] As a specific implementation manner, the catalyst III in step S3-1 is bis(diphenylphosphine)ferrocene (DPPF) and tri(dibenzylideneacetone)dipalladium (Pd2(dba)3); further, the molar ratio of bis(diphenylphosphine)ferrocene and tri(dibenzylideneacetone)dipalladium is 1:(1 to 1.1); it also includes a solvent, such as toluene; it includes an acid-base regulator, such as sodium tert-butoxide, sodium carbonate, and potassium carbonate; the catalyst can also be selected from other types as long as the reaction of S3-1 can be achieved.

[0137] As a specific implementation manner, the reaction temperature in step S3-1 is 60°C to 100°C, and the reaction time is 20 to 30 h; the reaction temperature can be any value among 60°C, 70°C, 80°C, 90°C, 100°C, or a range value between any two of them; the reaction time is any value among 20h, 22h, 24h, 26h, 28h, 30h, or a range value between any two of them.

[0138] As a specific implementation manner, in step S4, the molar ratio of intermediate III to sodium borohydride is 1:(9-11); within this ratio range, the molar ratio of sodium borohydride can be any value among 9, 10, 11 or a range value between any two of them; using this ratio, the aldehyde group on the benzene ring of intermediate III can be reduced to a hydroxyl group.

[0139] As a specific implementation manner, step S4 also includes a solvent, such as tetrahydrofuran.

[0140] As a specific implementation manner, the reaction process in step S4 includes a first reaction process and a second reaction process.

[0141] The reaction temperature of the first reaction process is -10°C to 10°C, and the reaction time is 1 to 5h; the reaction temperature can be any value among -10°C, -5°C, 0°C, 5°C, 10°C, or a range between any two values; the reaction time can be any value among 1, 2, 3, 4, 5, or a range between any two values;

[0142] The reaction temperature of the second reaction process is 20°C to 35°C, and the reaction time is 10 to 15h; the reaction temperature can be any value among 20°C, 25°C, 30°C, 35°C, or a range value between any two of them; the reaction time can be any value among 10h, 12h, 15h, or a range value between any two of them; the temperature of the second reaction process can also be room temperature or normal temperature.

[0143] As a specific implementation method, the product after the reaction in step S4 is purified to obtain intermediate IV; the purification process includes: extracting, drying, filtering, vacuum distillation, sedimentation treatment and suction filtration of the product after the reaction to obtain intermediate IV; specifically, the reaction product is quenched with water, the mixture is extracted with DCM, the organic phase is dried with anhydrous Mg2SO4, filtered, vacuum distilled, and finally precipitated with n-hexane / dichloromethane and suction filtered to obtain high-purity intermediate IV.

[0144] As a specific implementation, in step S5, the ratio of intermediate IV and acryloyl chloride is 1mmoL:(0.1-0.3)Ml; this ratio can be used to connect the acrylate group to the hydroxyl group of benzyl alcohol; the acrylate group can make the final compound have better film-forming properties after the polymerization reaction.

[0145] As a specific implementation, step S5 further includes a solvent, such as dichloromethane and triethylamine. The addition of triethylamine to the solvent of the present invention is suitable for acid binding agent and catalytic effect, so that the time of generating hydrogen chloride is faster.

[0146] As a specific implementation manner, the reaction temperature in step S5 is -10°C to 10°C, and the reaction time is 5 to 7h; the reaction temperature can be any value among -10°C, -5°C, 0°C, 5°C, 10°C, or a range value between any two thereof; the reaction time can be any value among 5h, 6h, 7h, or a range value between any two thereof.

[0147] As a specific implementation method, the product after the reaction in step S5 is purified to obtain intermediate V; the purification process includes: extracting, drying, filtering, vacuum distillation, sedimentation treatment and suction filtration of the product after the reaction to obtain intermediate V; more specifically, quenching the reaction with water, extracting the mixture with DCM, drying the organic phase with anhydrous Mg2SO4, filtering, vacuum distillation, and finally settling with n-hexane / dichloromethane and suction filtration to obtain intermediate V with high purity.

[0148] As a specific implementation, in step S6, the weight of the initiator is 0.5-1.5% of the weight of the intermediate V; the amount of the initiator is any value of 0.5%, 0.8%, 1.0%, 1.2%, 1.5% of the weight of the monomer or any range value between the two; the initiator is azobisisobutyronitrile; the initiator can also select other types of initiators according to actual conditions, as long as it can initiate the polymerization reaction of acrylate.

[0149] As a specific implementation, step S6 further includes a solvent, such as at least one of toluene, tetrahydrofuran and N-methylpyrrolidone.

[0150] As a specific implementation manner, the reaction process in step S6 includes a first reaction process and a second reaction process.

[0151] The reaction temperature of the first reaction process is 60°C to 75°C, and the reaction time is 2 to 4 hours; that is, the polymerization initiation temperature is any value among 60, 65, 70, 75, or a range value between any two of them; the polymerization reaction time is any value among 2, 3, 4 hours, or a range value between any two of them;

[0152] After the initiation reaction is carried out for the first reaction time, the temperature is then raised to carry out the second reaction process, the reaction temperature is 75°C to 95°C, and the reaction time is 48 to 72h; the reaction temperature can be any value among 75°C, 80°C, 85°C, 90°C, 95°C or a range value between any two thereof; the reaction time is any value among 48, 55, 60, 65, 70, 72h or a range value between any two thereof.

[0153] As a specific implementation manner, the product after the reaction in step S6 is purified to obtain the final compound; the purification process includes: crystallizing the product after the reaction with n-hexane or ethanol / dichloromethane, filtering, drying, and extracting with acetone solvent in sequence to obtain the compound.

[0154] The compound of the present invention is obtained by free radical polymerization of an Ar-substituted acrylic ester monomer V;

[0155]

[0156] Specifically, the free radical polymerization reaction of the present invention is to polymerize the acrylic ester monomer I at 65-85°C with azobisisobutyronitrile (AIBN) as a catalyst. The reaction bottle used in the experiment needs to be soaked and cleaned in potassium dichromate washing solution, then the salt layer on the inner wall is removed with saturated water vapor, and finally baked in a flame and cooled with nitrogen protection to achieve the purpose of removing oxygen on the bottle wall. Under the protection of nitrogen, the monomer V concentration is 0.1-1.0 mol / L and the AIBN concentration is 1.0-10.0×10 -3 mol / L toluene or tetrahydrofuran solution, stir with nitrogen. Add the above solution to the reaction bottle, cool with liquid nitrogen - evacuate - heat up - pass nitrogen, cycle three times to remove oxygen in the system; then seal the bottle and place it in a 65℃ oil bath for 2-3 hours, then heat it to 85℃, react for 72 hours, quench the reaction with methanol, and then precipitate with methanol to obtain a crude polymer product; extract the crude product with anhydrous ethanol to obtain a polymer material with a narrow molecular weight distribution.

[0157] As a more specific embodiment, the method of the present invention comprises:

[0158] Reaction step a: Weigh dithienopyrrole, 4-bromobenzaldehyde, palladium acetate, tri-tert-butylphosphine, sodium tert-butoxide (or potassium carbonate) and add them into a 100 mL double-necked reaction flask, use toluene as solvent, condense and reflux at 110°C under N2 gas for 48 hours. Cool to room temperature, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, distill under reduced pressure, and finally purify by column chromatography to obtain intermediate I solid powder;

[0159] Reaction step b: Weigh the intermediate I and add it to a 500mL three-necked flask, then add 30mL of dry THF, degas the mixture, flush it with N2 gas, and stir it at 0℃ for 10min. Then dissolve NBS in THF, add it dropwise to the mixture, and continue to react at 0℃ for 3 hours. Quench the reaction with 50mL of deionized water, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, and finally purify it by column chromatography to obtain the solid powder of intermediate II;

[0160] Reaction step c: weigh intermediate II, aniline fluorene or diphenylamine, Pd2(dba)3, DPPF (bis(diphenylphosphine)-ferrocene, organic metal catalyst), sodium tert-butoxide and toluene into a flask, react at 80°C for 24 hours under N2 gas, and then cool to room temperature. DCM extraction, drying over anhydrous magnesium sulfate, column chromatography with PE / DCM of 6 / 1 to obtain intermediate III;

[0161] Reaction step d: weigh intermediate III and dry THF, stir at 0°C for 10 min, add sodium borohydride (strong reducing agent) into the reaction system in three portions, continue stirring at 0°C for 3 hours, then move to room temperature for reaction for 12 hours, cool to room temperature, add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain intermediate IV;

[0162] Reaction step e: Weigh the intermediate IV, add 15 mL of dry DCM and 15 mL of dry triethylamine, flush with N2 to remove oxygen, stir at 0°C for 10 min, slowly drop acryloyl chloride and react for 6 hours. Add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain the intermediate V.

[0163] According to a fourth aspect of the present invention, a perovskite solar cell is provided, comprising a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a conductive metal layer; wherein the material of the hole transport layer comprises the above-mentioned hole transport material.

[0164] As a specific implementation, the material of the conductive glass layer is ITO or FTO glass; the material of the conductive metal layer is a composite material of copper and gold.

[0165] The above-mentioned compound prepared by the present invention has a high decomposition temperature as a hole transport material, has good thermal stability, and has good film-forming properties. It has good wettability with perovskite precursor solvents, which is beneficial to the crystallization and film formation of perovskite. The polymer hole transport material has good mobility, which is beneficial to the extraction and transmission of holes. It has a deeper HOMO energy level that matches that of perovskite, and can obtain good photoelectric conversion efficiency. The polymer hole transport material can be used in quasi-two-dimensional perovskite solar cells without being doped with any additives, and has repeatability. This type of compound has good application prospects.

[0166] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0167] The raw materials used in the following embodiments or process synthesis routes 7, 8, 9, and 10 of the present invention are all commercially available, and the abbreviations of the chemical substances are explained as follows:

[0168] NBS: bromosuccinimide; DPPF: bis(diphenylphosphine)ferrocene; Pd2(dba)3: tri(dibenzylideneacetone)dipalladium; Pd(OAc)2: palladium acetate; t-Bu3P: tri-tert-butylphosphine; toluene: toluene; THF: tetrahydrofuran; NaOtBu: sodium tert-butoxide; P(t-Bu)3: p-tri-tert-butylphosphine; ethanol: ethanol; Triethylamine: triethylamine; AIBN: azobisisobutyronitrile; DCM: dichloromethane; PC61BM: fullerene derivative, (6,6)-phenyl-C61-butyric acid methyl ester.

[0169] Example 1 (PMA-DTP-1, synthesis route as formula 7)

[0170]

[0171] Synthesis of compound 2: Compound 1 (1.79 g, 10 mmol), 4-bromobenzaldehyde (2.4 g, 13 mmol), palladium acetate (0.045 g, 0.2 mmol), tri-tert-butylphosphine (0.82 g, 0.4 mmol), potassium carbonate (15 mmol) were added to a 100 mL double-necked reaction flask, toluene (40 mL) was used as solvent, and condensed and refluxed at 110 ° C under N2 gas for 48 hours. Cool to room temperature, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, and finally purify by column chromatography (PE: DCM = 10: 1) to obtain 1.7 g of solid powder of compound 2, with a yield of 60%.

[0172] Synthesis of compound 3: Weigh compound 2 (0.85 g, 3 mmol) into a 500 mL three-necked flask, then add 30 mL of dry THF, degas the mixture, flush with N2 gas, and stir at 0°C for 10 min. Then NBS (1.07 g, 6 mmol) was dissolved in THF (20 mL), added dropwise to the mixture, and the reaction continued at 0°C for 16 hours. The reaction was quenched with 50 mL of deionized water, the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain 1.2 g of compound 3 solid, with a yield of 90%.

[0173] Synthesis of compound 6: Compound 4 (1.1 g, 4 mmol) (compound 4 is 3-bromo-9,9-dimethyl-9H-fluorene), compound 5 (0.52 g, 4.2 mmol), Pd2(dba)3 (0.18 g, 0.2 mmol), DPPF (0.11 g, 0.2 mmol), sodium tert-butoxide (0.38 g, 4 mmol) and toluene were weighed and added to a flask, and reacted at 120°C for 12 hours. DCM extraction, drying over anhydrous magnesium sulfate, column chromatography with PE / DCM of 6 / 1 to obtain 0.85 g of compound 6 (compound 6 is 4-(2,6-dibromo-4H-dithiophene [3,2-b:2',3'-d] pyrrol-4-yl) benzaldehyde), with a yield of 67.5%.

[0174] Synthesis of compound 7: Weigh compound 3 (0.88 g, 2 mmol), compound 6 (1.58 g, 5 mmol), sodium tert-butoxide (0.24 g, 2.5 mmol), palladium acetate (21 mg, 0.09 mmol), 0.3 ml tri-tert-butylphosphine toluene solution, 60 ml toluene were added into a flask, reacted at 85°C for 12 hours and then cooled to room temperature. Column chromatography with PE / DCM of 6 / 1 gave 1.27 g of compound 7 with a yield of 70%.

[0175] Synthesis of compound 8: Weigh compound 7 (0.91 g, 1 mmol), add 40 mL of dry THF, stir at 0°C for 10 min, add sodium borohydride (0.38 g, 10 mmol) into the reaction system in three portions, stir at 0°C for 3 hours, then move to room temperature to react for 13 hours, cool to room temperature, add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane and filter to obtain 0.81 g of compound 8 solid powder with a yield of 90%.

[0176] Synthesis of compound 9: Weigh compound 8 (0.92 g, 1 mmol), add 15 mL of dry DCM and 15 mL of dry triethylamine, flush with N2 to deoxygenate, stir at 0°C for 10 min, slowly drop acryloyl chloride (0.2 mL) and react for 6 hours. Add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain 0.87 g of solid powder of compound 9 with a yield of 90%.

[0177] Synthesis of PMA-DTP-1: Weigh 300 mg of compound 9 and 1% monomer mass ratio of azobisisobutyronitrile (3 mg) and add them to a toluene solution (or tetrahydrofuran, N-methylpyrrolidone), freeze-dry with liquid nitrogen, evacuate for 1 minute, and then fill with nitrogen. Repeat three times and seal. Initiate at 65°C for 3 hours, and react at 85°C for 3 days. After the reaction is completed, cool to room temperature, crystallize with n-hexane (ethanol) / dichloromethane, filter and dry, use acetone as solvent, and extract with a Soxhlet extractor for three days to obtain PMA-DTP-1 (160 mg); the chemical structure analysis spectrum of the compound is shown as follows Figure 1 shown.

[0178] Example 2 (PMA-DTP-2, synthesis route as formula 8)

[0179]

[0180] Synthesis of compound 2: Compound 1 (1.79 g, 10 mmol), 4-bromobenzaldehyde (2.4 g, 13 mmol), palladium acetate (0.045 g, 0.2 mmol), tri-tert-butylphosphine (0.82 g, 0.4 mmol), potassium carbonate (15 mmol) were added to a 100 mL double-necked reaction flask, toluene (40 mL) was used as solvent, and condensed and refluxed at 110 ° C under N2 gas for 48 hours. Cool to room temperature, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, and finally purify by column chromatography (PE: DCM = 10: 1) to obtain 1.7 g of solid powder of compound 2, with a yield of 60%.

[0181] Synthesis of compound 3: Weigh compound 2 (0.85 g, 3 mmol) into a 500 mL three-necked flask, then add 30 mL of dry THF, degas the mixture, flush with N2 gas, and stir at 0°C for 10 min. Then NBS (1.07 g, 6 mmol) was dissolved in THF (20 mL), added dropwise to the mixture, and the reaction continued at 0°C for 16 hours. The reaction was quenched with 50 mL of deionized water, the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain 1.2 g of compound 3 solid, with a yield of 90%.

[0182] Synthesis of compound 6: Compound 4 (1.1 g, 4 mmol), compound 5 (0.52 g, 4.2 mmol), Pd2(dba)3 (0.18 g, 0.2 mmol), DPPF (0.11 g, 0.2 mmol), sodium tert-butoxide (0.38 g, 4 mmol) and toluene were weighed and added into a flask, and reacted at 120°C for 12 hours. DCM extraction, drying over anhydrous magnesium sulfate, and column chromatography with PE / DCM of 6 / 1 gave 0.85 g of compound 6, with a yield of 67.5%.

[0183] Synthesis of compound 7: Weigh compound 3 (0.88 g, 2 mmol), compound 6 (1.66 g, 5 mmol), sodium tert-butoxide (0.24 g, 2.5 mmol), palladium acetate (21 mg, 0.09 mmol), 0.3 ml tri-tert-butylphosphine toluene solution, 60 ml toluene were added into a flask, reacted at 85°C for 12 hours and then cooled to room temperature. Column chromatography with PE / DCM of 6 / 1 gave 1.31 g of compound 7 with a yield of 70%.

[0184] Synthesis of compound 8: Weigh compound 7 (0.94 g, 1 mmol), add 40 mL of dry THF, stir at 0°C for 10 min, add sodium borohydride (0.38 g, 10 mmol) into the reaction system in three portions, stir at 0°C for 3 hours, then move to room temperature and react for 13 hours, cool to room temperature, add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane and filter to obtain 0.81 g of compound 8 solid powder with a yield of 90%.

[0185] Synthesis of compound 9: Weigh compound 8 (0.94 g, 1 mmol), add 15 mL of dry DCM and 15 mL of dry triethylamine, flush with N2 to deoxygenate, stir at 0°C for 10 min, slowly drop acryloyl chloride (0.2 mL) and react for 6 hours. Add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain 0.87 g of solid powder of compound 9 with a yield of 90%.

[0186] Synthesis of PMA-DTP-2: Weigh 300 mg of compound 9 and 1% monomer mass ratio of azobisisobutyronitrile (3 mg) and add them to a toluene solution (or tetrahydrofuran, N-methylpyrrolidone), freeze-dry with liquid nitrogen, evacuate for 1 minute, and then fill with nitrogen. Repeat three times and seal. Initiate at 65°C for 3 hours, and react at 85°C for 3 days. After the reaction is completed, cool to room temperature, crystallize with n-hexane (ethanol) / dichloromethane, filter and dry, use acetone as solvent, and extract with a Soxhlet extractor for three days to obtain PMA-DTP-2 (160 mg); the chemical structure analysis spectrum of the compound is shown as follows Figure 2 shown.

[0187] Example 3 (PMA-DTP-3, synthesis route as formula 9)

[0188]

[0189] Synthesis of compound 2: Compound 1 (1.79 g, 10 mmol), 4-bromobenzaldehyde (2.4 g, 13 mmol), palladium acetate (0.045 g, 0.2 mmol), tri-tert-butylphosphine (0.82 g, 0.4 mmol), potassium carbonate (15 mmol) were added to a 100 mL double-necked reaction flask, toluene (40 mL) was used as solvent, and condensed and refluxed at 110 ° C under N2 gas for 48 hours. Cool to room temperature, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, and finally purify by column chromatography (PE: DCM = 10: 1) to obtain 1.7 g of solid powder of compound 2, with a yield of 60%.

[0190] Synthesis of compound 3: Weigh compound 2 (0.85 g, 3 mmol) into a 500 mL three-necked flask, then add 30 mL of dry THF, degas the mixture, flush with N2 gas, and stir at 0°C for 10 min. Then NBS (1.07 g, 6 mmol) was dissolved in THF (20 mL), added dropwise to the mixture, and the reaction continued at 0°C for 16 hours. The reaction was quenched with 50 mL of deionized water, the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain 1.2 g of compound 3 solid, with a yield of 90%.

[0191] Synthesis of compound 5: Weigh compound 3 (0.88 g, 2 mmol), compound 4 (1.15 g, 5 mmol), sodium tert-butoxide (0.24 g, 2.5 mmol), palladium acetate (21 mg, 0.09 mmol), 0.3 ml tri-tert-butylphosphine toluene solution, 60 ml toluene were added into a flask, reacted at 85°C for 12 hours and then cooled to room temperature. Column chromatography with PE / DCM of 6 / 1 gave 1.02 g of compound 7 with a yield of 70%.

[0192] Synthesis of compound 6: Weigh compound 5 (0.74 g, 1 mmol), add 40 mL of dry THF, stir at 0°C for 10 min, add sodium borohydride (0.38 g, 10 mmol) into the reaction system in three portions, continue stirring at 0°C for 3 hours, continue the reaction for 13 hours, cool to room temperature, add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane and filter to obtain 0.66 g of compound 6 solid powder with a yield of 90%.

[0193] Synthesis of compound 7: Weigh compound 6 (0.74 g, 1 mmol), add 15 mL of dry DCM and 15 mL of dry triethylamine, flush with N2 to deoxygenate, stir at 0°C for 10 min, slowly drop acryloyl chloride (0.2 mL) and react for 6 hours. Add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain 0.64 g of solid powder of compound 7 with a yield of 90%.

[0194] Synthesis of PMA-DTP-3: Weigh 300 mg of compound 7 and 1% monomer mass ratio of azobisisobutyronitrile (3 mg) and add them to a toluene solution (or tetrahydrofuran, N-methylpyrrolidone), freeze-dry with liquid nitrogen, evacuate for 1 minute, and then fill with nitrogen. Repeat three times and seal. Initiate at 65°C for 3 hours, and react at 85°C for 3 days. After the reaction is completed, cool to room temperature, crystallize with n-hexane (ethanol) / dichloromethane, filter and dry, use acetone as solvent, and extract with a Soxhlet extractor for three days to obtain PMA-DTP-3 (160 mg); the chemical structure analysis spectrum of the compound is shown as follows Figure 3 shown.

[0195] Example 4 (PMA-DTP-4, synthesis route as formula 10)

[0196]

[0197] Synthesis of compound 2: Compound 1 (1.79 g, 10 mmol), 4-bromobenzaldehyde (2.4 g, 13 mmol), palladium acetate (0.045 g, 0.2 mmol), tri-tert-butylphosphine (0.82 g, 0.4 mmol), potassium carbonate (15 mmol) were added to a 100 mL double-necked reaction flask, toluene (40 mL) was used as solvent, and condensed and refluxed at 110 ° C under N2 gas for 48 hours. Cool to room temperature, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, and finally purify by column chromatography (PE: DCM = 10: 1) to obtain 1.7 g of solid powder of compound 2, with a yield of 60%.

[0198] Synthesis of compound 3: Weigh compound 2 (0.85 g, 3 mmol) into a 500 mL three-necked flask, then add 30 mL of dry THF, degas the mixture, flush with N2 gas, and stir at 0°C for 10 min. Then NBS (1.07 g, 6 mmol) was dissolved in THF (20 mL), added dropwise to the mixture, and the reaction continued at 0°C for 16 hours. The reaction was quenched with 50 mL of deionized water, the mixture was extracted with DCM, the organic phase was dried over anhydrous Mg2SO4, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain 1.2 g of compound 3 solid, with a yield of 90%.

[0199] Synthesis of compound 5: Weigh compound 3 (0.88 g, 2 mmol), compound 4 (1.3 g, 5 mmol), sodium tert-butoxide (0.24 g, 2.5 mmol), palladium acetate (21 mg, 0.09 mmol), 0.3 ml tri-tert-butylphosphine toluene solution, 60 ml toluene were added into a flask, reacted at 85°C for 12 hours and then cooled to room temperature. Column chromatography with PE / DCM of 6 / 1 gave 1.12 g of compound 7 with a yield of 70%.

[0200] Synthesis of compound 6: Weigh compound 5 (0.81 g, 1 mmol), add 40 mL of dry THF, stir at 0°C for 10 min, add sodium borohydride (0.38 g, 10 mmol) into the reaction system in three portions, continue stirring at 0°C for 3 hours, continue the reaction for 13 hours, cool to room temperature, add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane and filter to obtain 0.66 g of solid powder of compound 6 with a yield of 90%.

[0201] Synthesis of compound 7: Weigh compound 6 (0.81 g, 1 mmol), add 15 mL of dry DCM and 15 mL of dry triethylamine, flush with N2 to deoxygenate, stir at 0°C for 10 min, slowly drop acryloyl chloride (0.2 mL) and react for 6 hours. Add 50 mL of water to quench the reaction, extract the mixture with DCM, dry the organic phase with anhydrous Mg2SO4, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain 0.77 g of solid powder of compound 7 with a yield of 90%.

[0202] Synthesis of PMA-DTP-4: Weigh 300 mg of compound 7 and 1% monomer mass ratio of azobisisobutyronitrile (recrystallized from ethanol in advance; 3 mg) and add toluene solution (or tetrahydrofuran, N-methylpyrrolidone), freeze-dry with liquid nitrogen, evacuate for 1 minute, and then fill with nitrogen. Repeat three times and seal. After initiation at 65°C for 3 hours, react at 85°C for 3 days. After the reaction is completed, cool to room temperature, use n-hexane (ethanol) / dichloromethane for crystallization, filter and dry, use acetone as solvent, and extract with a Soxhlet extractor for three days to obtain PMA-DTP-4 (160 mg); the chemical structure analysis spectrum of the compound is shown as follows Figure 4 shown.

[0203] In Examples 1 to 4 of the present invention, four compounds, PMA-DTP-1, PMA-DTP-2, PMA-DTP-3, and PMA-DTP-4, were prepared; compounds PMA-DTP-1 and PMA-DTP-3 were used as representative hole transport materials to prepare perovskite solar cells.

[0204] Application Example 1 (Perovskite Solar Cell)

[0205] The method for preparing an inverse quasi-two-dimensional perovskite solar cell comprises the following steps:

[0206] (1) Cleaning ITO glass 1: Use deionized water, acetone and ethanol to ultrasonically clean the ITO glass sheet for 15 to 20 minutes in sequence, then use a N2 air gun to blow dry the residual solvent on the ITO surface, then perform oxygen plasma treatment for 10 to 15 minutes, and then transfer the ITO glass sheet to a nitrogen glove box.

[0207] (2) Preparation of hole transport layer 2: 3-15 mg of polyacrylate (PMA-DTP-1 of Example 1) as a hole transport material was weighed and completely dissolved in 1 mL of chlorobenzene solution. An appropriate amount of the solution was evenly dropped onto the ITO glass substrate, and spin-coated at 4000-5000 rpm for 20-30 seconds, and then annealed at 90-110° C. for 10 minutes.

[0208] (3) Preparation of perovskite layer 3: The ITO / hole transport layer substrate obtained above is cooled to room temperature, preheated at 130-140°C for 3-5 minutes, 50 μl of perovskite solution is spread over the ITO / hole transport layer substrate, spin coated at 3000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 10 minutes to prepare a perovskite layer. The perovskite solution is prepared by mixing 3-bromo-benzylammonium iodide or 3-chlorobenzylammonium iodide, methylammonium chloride, and lead iodide in DMF and DMSO in a certain molar ratio;

[0209] (4) Preparation of electron transport layer 4: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μl of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 to 50 seconds;

[0210] (5) Preparation of composite electrode layer 5: The above substrate is placed in a vacuum evaporation chamber, and Cu (film thickness 6 nm) and Au (film thickness 80 nm) are evaporated on the PC61BM layer, respectively, to obtain an inverse quasi-two-dimensional perovskite solar cell with the structure shown in FIG. Figure 5 shown.

[0211] Application Example 2 (Perovskite Solar Cell)

[0212] The method for preparing an inverse quasi-two-dimensional perovskite solar cell comprises the following steps:

[0213] (1) ITO glass 1 cleaning: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone and ethanol for 15 to 20 minutes in sequence, and then the residual solvent on the ITO surface was blown dry with a N2 air gun. The ITO glass sheet was then treated with oxygen plasma for 10 to 15 minutes, and then the ITO glass sheet was transferred to a nitrogen glove box.

[0214] (2) Preparation of hole transport layer 2: 3-15 mg of polyacrylate (PMA-DTP-3 of Example 3) as a hole transport material was weighed and completely dissolved in 1 mL of chlorobenzene solution. An appropriate amount of the solution was evenly dripped onto the ITO glass substrate, and spin-coated at 4000-5000 rpm for 20-30 seconds, and then annealed at 90-110° C. for 10 minutes.

[0215] (3) Preparation of perovskite layer 3: The ITO / hole transport layer substrate obtained above is cooled to room temperature, preheated at 130-140°C for 3-5 minutes, 50 μl of perovskite solution is spread over the ITO / hole transport layer substrate, spin coated at 3000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 10 minutes to prepare a perovskite layer. The perovskite solution is prepared by mixing 3-bromo-benzylammonium iodide or 3-chlorobenzylammonium iodide, methylammonium chloride, and lead iodide in DMF and DMSO in a certain molar ratio;

[0216] (4) Preparation of electron transport layer 4: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μl of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 to 50 seconds;

[0217] (5) Preparation of composite electrode 5: The above substrate is placed in a vacuum evaporation box, and Cu (film thickness 6 nm) and Au (film thickness 80 nm) are evaporated on the PC61BM layer respectively, to obtain an inverse quasi-two-dimensional perovskite solar cell.

[0218] Comparative Application Example 1 (Perovskite Solar Cell)

[0219] The difference between Comparative Application Example 1 and Application Example 1 is that the hole transport material in step (2) is poly(3-hexylthiophene) (P3HT).

[0220] Comparative Application Example 2 (Perovskite Solar Cell)

[0221] The difference between Comparative Application Example 2 and Application Example 1 is that the hole transport material in step (2) is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA).

[0222] The decomposition temperature, HOMO energy level and hole mobility of Example 1, Example 2, Example 3 and Example 4 prepared as above were tested. The test results are shown in Table 1.

[0223] Table 1

[0224] Example Decomposition temperature / ℃ HOMO level / eV <![CDATA[Hole mobility / cm 2 ·V -1 S -1 > Example 1 349 -5.38 <![CDATA[6.35×10 -4 ]]> Example 2 322 -5.32 <![CDATA[3.67×10 -4 ]]> Example 3 278 -5.22 <![CDATA[9.66×10 -5 ]]> Example 4 378 -5.25 <![CDATA[1.35×10 -4 ]]>

[0225] The perovskite solar cells prepared in the above-mentioned Examples 1, 2, 3 and 4 were tested for photoelectric conversion efficiency, open circuit voltage, short circuit current and fill factor. The test results are shown in Table 2.

[0226] Table 2

[0227] Example Photoelectric conversion efficiency / % Open circuit voltage / V <![CDATA[Short-circuit current / mA·cm -2 > Fill factor / % Example 1 20.53 1.19 21.32 81 Example 2 19.78 1.18 21.22 79 Example 4 19.13 1.18 20.79 78 Example 4 18.69 1.18 21.05 76

[0228] By testing the performance of the perovskite solar cells prepared in Application Examples 1 and 2 of the present invention, it is found that they have excellent performance in terms of decomposition temperature, HOMO energy level, hole mobility, photoelectric conversion efficiency, etc.; this indicates that the polyacrylate compounds prepared by the present invention can be used as hole transport materials in perovskite solar cells.

[0229] Comparative Application Examples 1 and 2 use conventional hole transport materials that are also polymers with thiophene, benzene or amine structures. PTAA has poor wettability, which will hinder the crystallization of perovskite; its excessive intermolecular distance and steric hindrance lead to low conductivity, and it is difficult to form a strong interaction with the perovskite layer to reduce interface defects [59,79], which limits the further improvement of PCE. In addition, PTAA is expensive, which is not conducive to its large-scale commercial application. Poly (3-hexylthiophene) (P3HT), which is also a classic hole transport material, is expected to help realize efficient and stable perovskite batteries due to its advantages such as low synthesis cost, good batch reproducibility, high intrinsic mobility and good film morphology stability; however, P3HT still has problems such as energy level mismatch and poor interface contact when used in perovskite batteries.

[0230] In the polyacrylate structure provided by the present invention, acrylate is used as a polymerization monomer, and the molecular structure of the compound also includes a thiophene benzoate structure containing an Ar long side chain. The combined action of multiple groups enables it to have good solubility, high stability, film-forming property, high hole mobility and an energy level matching that of perovskite, which can promote the crystallization and film-forming property of the perovskite layer, and ultimately improve the battery performance and the photoelectric conversion efficiency.

[0231] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0232] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A compound, characterized in that The structure of the compound is shown in Formula 1: Among them, 10 <n <10000, n is an integer; Ar is an aniline fluorene group or a diphenylamine group.

2. The compound according to claim 1, characterized in that The chemical structure of the aniline fluorene group is shown in Formula 2 or Formula 3: The structure of the diphenylamine group is shown in Formula 4 or Formula 5:

3. The method for preparing the compound according to claim 1 or 2, characterized in that: The method comprises the following steps: Step S1: reacting dithienopyrrole, 4-bromobenzaldehyde and catalyst I under nitrogen conditions to obtain intermediate I; Step S2: reacting the intermediate I with bromosuccinimide to obtain intermediate II; Step S3: reacting the intermediate II, aniline fluorene or diphenylamine substances and catalyst II under nitrogen conditions to obtain intermediate III; Step S4: reacting the intermediate III with sodium borohydride to obtain intermediate IV; Step S5: reacting the intermediate IV with acryloyl chloride to obtain intermediate V; Step S6: mixing the intermediate V and the initiator, and reacting them to obtain the compound.

4. The method for preparing the compound according to claim 3, characterized in that: In the step S1, the molar ratio of the dithienopyrrole, the 4-bromobenzaldehyde and the catalyst is (8-12): (11-15): (0.5-0.7); And / or, the catalyst I is palladium acetate and tri-tert-butylphosphine; Preferably, the molar ratio of the palladium acetate to the tri-tert-butyl phosphine in step S1 is 1:(1.5-2.5); And / or, the step S1 further comprises a solvent, preferably the solvent is toluene; And / or, the step S1 further comprises an acid-base regulator, preferably the acid-base regulator is sodium tert-butoxide, sodium carbonate, potassium carbonate; And / or, the reaction temperature in step S1 is 100° C. to 120° C., and the reaction time is 45 to 50 h; And / or, the mixture after the reaction in step S1 is purified to obtain the intermediate I; Preferably, the purification process in step S1 comprises: extracting, drying, filtering, distilling under reduced pressure and column chromatography on the mixture in sequence to obtain the intermediate I.

5. The method for preparing the compound according to claim 3 or 4, characterized in that: In the step S2, the molar ratio of the intermediate I to the bromosuccinimide is 1:(1.5-2.5); And / or, the step S2 further comprises a solvent, preferably the solvent is tetrahydrofuran; And / or, the reaction temperature in step S2 is -10°C to 10°C, and the reaction time is 1 to 5 hours; And / or, the mixture after the reaction in step S2 is purified to obtain the intermediate II; Preferably, the purification process in step S2 comprises: extracting, drying, filtering, distilling under reduced pressure and column chromatography on the mixture in sequence to obtain the intermediate II.

6. The method for preparing the compound according to any one of claims 3 to 5, characterized in that: In the step S3, the molar ratio of the intermediate II, the aniline fluorene compound or the diphenylamine compound, and the catalyst II is (1.5-2.5): (4~6):(0.35~0.45); Preferably, the aniline fluorene compound is N-(4-methoxyphenyl)-9,9-dimethyl-9H-fluorene-3-amine or 9,9-dimethyl-N-(4-(methylthio)phenyl)-9H-fluorene-3-amine; Preferably, the diphenylamine compound is di(4-methoxyphenyl)amine or bis(4-(methylthio)phenyl)amine; And / or, the catalyst II is palladium acetate and tri-tert-butylphosphine; Preferably, the molar ratio of the palladium acetate to the tri-tert-butyl phosphine in step S3 is 1:(2.5-3.5); And / or, the step S3 further comprises a solvent, preferably the solvent is toluene; And / or, the step S3 further comprises an acid-base regulator, preferably the acid-base regulator is sodium tert-butoxide, sodium carbonate, potassium carbonate; And / or, the reaction temperature in step S3 is 75°C to 100°C, and the reaction time is 4 to 8 hours; And / or, the mixture after the reaction in step S3 is purified to obtain the intermediate III; Preferably, the purification process in step S3 comprises: extracting, drying, and column chromatography the mixture in sequence to obtain the intermediate III; Preferably, the preparation step S3-1 of the aniline fluorene compound comprises: mixing a fluorene compound, an aniline compound and a catalyst III, and reacting them to obtain the aniline fluorene compound; Preferably, the molar ratio of the fluorene compound, the aniline compound and the catalyst III is (3.5-4.5): (3.7-4.7): (0.35-0.45); Preferably, the catalyst III is bis(diphenylphosphine)-ferrocene and tris(dibenzylideneacetone)dipalladium; Preferably, the molar ratio of the bis(diphenylphosphine)-ferrocene to tris(dibenzylideneacetone)dipalladium in the catalyst III is 1:(1-1.1); Preferably, the step S3-1 further comprises a solvent, preferably toluene; Preferably, the step S3-1 further comprises an acid-base regulator, preferably sodium tert-butoxide, sodium carbonate, potassium carbonate; Preferably, the reaction temperature in step S3-1 is 70°C to 90°C, and the reaction time is 20 to 28 hours.

7. The method for preparing the compound according to any one of claims 3 to 6, characterized in that: In the step S4, the molar ratio of the intermediate III to the sodium borohydride is 1:(9-11); And / or, the step S4 further comprises a solvent, preferably the solvent is tetrahydrofuran; And / or, the reaction process in step S4 includes a first reaction process and a second reaction process; The reaction temperature of the first reaction process is -10°C to 10°C, and the reaction time is 1 to 5 hours; The reaction temperature of the second reaction process is 20°C to 35°C, and the reaction time is 10 to 15 hours; And / or, the mixture after the reaction in step S4 is purified to obtain the intermediate IV; Preferably, the purification process in step S4 comprises: extracting, drying, filtering, distilling under reduced pressure, settling and filtering the mixture in sequence to obtain the intermediate IV.

8. The method for preparing the compound according to any one of claims 3 to 7, characterized in that: In the step S5, the ratio of the intermediate IV to the acryloyl chloride is 1 mmoL: (0.1-0.3) mL; And / or, the step S5 further comprises a solvent, preferably the solvent is dichloromethane and triethylamine; And / or, the reaction temperature in step S5 is -10°C to 10°C, and the reaction time is 5 to 7 hours; And / or, the mixture after the reaction in step S5 is purified to obtain the intermediate V; Preferably, the purification process in step S5 comprises: extracting, drying, filtering, distilling under reduced pressure, settling and filtering the mixture in sequence to obtain the intermediate V; and / or, in step S6, the weight of the initiator is 0.5-1.5% of the weight of the intermediate V; Preferably, the initiator is azobisisobutyronitrile; And / or, the step S6 further comprises a solvent, preferably the solvent is at least one of toluene, tetrahydrofuran and N-methylpyrrolidone; And / or, the reaction process in step S6 includes a first reaction process and a second reaction process; Wherein, the reaction temperature of the first reaction process is 60°C to 75°C, and the reaction time is 2 to 4 hours; The reaction temperature of the second reaction process is 55°C to 95°C, and the reaction time is 48 to 72 hours; And / or, the mixture after the reaction in step S6 is purified to obtain the final compound; Preferably, the purification process in step S6 comprises: sequentially subjecting the mixture to n-hexane or ethanol / dichloromethane crystallization, suction filtration, drying, and acetone solvent extraction to obtain the compound.

9. A hole transport material, characterized in that It includes the compound according to claim 1 or 2 or the compound prepared by the preparation method according to any one of claims 3 to 8.

10. A perovskite solar cell, characterized in that: It comprises a conductive glass layer, a hole transport layer, a perovskite layer, an electron transport layer and a conductive metal layer; wherein the material of the hole transport layer comprises the hole transport material according to claim 9; Preferably, the material of the conductive glass layer is ITO or FTO glass; the material of the conductive metal layer is a composite material of copper and gold; Preferably, the perovskite solar cell is an inverted perovskite solar cell.